Gender Equity in Muslim Family Law: Modern and Contemporary ‘Ulamā’s View - Begum, Mohamed Sulthan Ismiya; Ismail, Indriaty; Yaakob, Zul'azmi; Razick, Ahamed Sarjoon; Abdullah, Mohamed Mahroof Ali (Al-Ahkam, 2024)
The concept of equality has been a rhetoric of increasing importance globally today. This concept teaches that men and women are equal in all aspects without distinction. The Islamic teaching totally reject this concept. Therefore, the main feminist movement claims that Islam is a anti-religion to equality. The equality concept of Islam is quite different from the Western perspective. Hence, this study focuses on the ‘ulamā’s view on some important aspects related to equity, especially the nature of different gender and different responsibilities, divorce rights, polygamy, testimony, and inheritable rights based on narrative review. It employs a qualitative approach, where the relevant document is based on primary and secondary sources such as books, journals and website articles and videos. The data collected in this regard were analyzed using the content analyzing method. The findings show that the modern and contemporary ‘ulamā’s opinion aligns with Islam’s principle of equity, emphasizing the reality and justice behind the concept of equity. Through the understanding and practice of Islamic doctrine can establish a fair equality in the world.